2017
DOI: 10.3947/ic.2017.49.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection after Renal Transplantation: Occurrence, Clinical Features, and the Cutoff for Antigenemia in a University Hospital in Brazil

Abstract: BackgroundCytomegalovirus (CMV) is the main infectious agent causative of morbidity and mortality in transplant recipients. This study aimed to describe the occurrence and clinical features of CMV infection, and the optimum antigenemia assay cutoff associated with symptomatic infection.Materials and MethodsThis was a cohort study that investigated 87 patients undergoing renal transplantation. The patients were monitored with the CMV antigenemia assay performed weekly for the first 3 months post-transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
(35 reference statements)
1
13
2
Order By: Relevance
“…Deceased donor transplant was identified in the multivariable analysis to be noticeably associated with CMV viremia, as living donation had an odds ratio of 0.54 for the development of CMV viremia (p = 0.005). This is consistent with the literature [14,22]. Further associations found were the age of the donor (p = 0.004) and the number of rejection episodes (p ≤ 0.001), while the use of cyclosporine A was protective (p = 0.024).…”
Section: Discussionsupporting
confidence: 91%
“…Deceased donor transplant was identified in the multivariable analysis to be noticeably associated with CMV viremia, as living donation had an odds ratio of 0.54 for the development of CMV viremia (p = 0.005). This is consistent with the literature [14,22]. Further associations found were the age of the donor (p = 0.004) and the number of rejection episodes (p ≤ 0.001), while the use of cyclosporine A was protective (p = 0.024).…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study from this center, the incidence of CMV with preventive therapy was reported as 17.8% (Corona-Nakamura et al 2009) compared with other reports that have described higher incidences (43.1%-63.2%) (Pretagostini et al 2017;Henrique Pinto et al 2016;de Matos et al, 2017). Current recommendations demonstrate superiority with the use of prophylaxis in preventive therapy in D+/R-; however, superiority is limited to few trials in the R+ group (Paya et al 2004;Humar et al 2010), and both strategies for prevention (preventive therapy or prophylaxis) are considered feasible options in R+ (Kotton et al 2018;Manuel et al 2013;Razonable 2020).…”
Section: Discussionmentioning
confidence: 82%
“…Cytomegalovirus (CMV) is a common complication in solid organ transplant recipients, and it can present as a primary infection, secondary infection, or be reactivate from a latent reserve (Koval 2018). In renal transplant recipients (RTR), the incidence of CMV infection or CMV disease (CMVI/CMVD) varies from 17.8%-63.2% (Helantera et al 2014;Chiasakul et al 2015;Corona-Nakamura et al 2009;de Matos et al, 2017;Felipe et al 2019;Ricart et al 2005;Henrique Pinto et al 2016;Minz et al 2020), and its presence is associated with a reduction in glomerular filtration rate (GFR), acute or chronic rejection (AR), opportunistic infection, high cardiovascular risk, and decrease in survival of the graft and the patient (Viot et al 2015;Courivaud et al 2013;Meijers et al 2015;Hodson et al 2013;Stern et al 2014). The following have all been documented as risk factors for CMV: serology test: IgG-positive donor (D) and IgG-negative recipient (D+/R-); anti-rejection therapy; female sex; advanced age; recipients from a deceased donor; transfusions; HLA-B44; absence and/or short lengths of antiviral prophylaxis treatment; and the use of prednisone (PDN), mycophenolate mofetil (MMF), tacrolimus (TAC), belatacept, or anti-thymocyte globulin (ATG) (Felipe et al 2019;Meije et al 2014;Viot et al 2015;ter Meulen et al, 2000;Wagner et al 2015;Futohi et al 2015;Ricart et al 2005;Bataille et al 2010;Chiasakul et al 2015;Diaz et al 2014;Kotton et al 2018;Abou-Ayache et al 2008;Brennan et al 1997;Humar et al 2010;Razonable et al 2001;Lucia et al 2014;Nafar et al 2014;Vacher-Coponat et al 2006;…”
Section: Introductionmentioning
confidence: 99%
“…While this figure appears higher than the reported incidence of CMV infections (~20– 40%) at other centres, we recognise that follow-up duration, diagnostic thresholds and prophylaxis strategies used at different centres were variable and may therefore account for the differences observed. 3,10,1922 Another reason for the higher reported incidence of CMV infections in our study is attributed to the fact that we had defined CMV infection as the presence of any detectable CMV in body fluid or tissue specimen, and reflected CMV reactivation in the post-transplant recipient. It is important to note that the overall incidence of CMV disease was relatively low (5.7% and 2.3% in Protocols 1 and 2, respectively), and only one patient (who received Protocol 1) developed tissue-invasive disease with CMV retinitis.…”
Section: Discussionmentioning
confidence: 79%
“…24 In our multivariate analyses, high CMV risk (determined by CMV D+/R-serostatus and receipt of thymoglobulin) and deceased donor transplant were independently associated with a higher risk of CMV infection, not choice of prophylaxis regimen, consistent with findings observed at other centres. 19,20,25 Prophylaxis strategies alone are insufficient to reduce the incidence of post-transplant infections, and two key areas could be reviewed to improve CMV outcomes: (a) the role of evaluating CMV-specific immunity prior to the discontinuation of antiviral therapy, and (b) the need for individualised immunosuppression dosing as opposed to a protocol-driven approach. CMV-specific immunoassays have been developed, and they are increasingly being evaluated for clinical use to identify patients who may be at high risk of CMV infection/disease.…”
Section: Discussionmentioning
confidence: 99%